A critique of neo-mercantilist analyses of Icelandic political economy and crisis. (October 2015) - Belfrage, Claes; Bergmann, Eirikur; Berry, David M.
Iceland's journey from rags to riches in the 20th century is related, in the dominant discourse, to its gaining independence in 1944. This discourse played a significant role in both the legitimation of the finance-dominated growth model in the 1990s and 2000s and in the latter's defence as it came under scrutiny before its collapse in October 2008. It is therefore ironic – or perhaps, in some sense, logical – to find dominant analyses of the crisis arising from the neo-mercantilist tradition. Drawing on Marxist critiques of neo-mercantilism, we challenge these interventions and thus seek to redress the neglect of social struggle in the dominant discourse.